A time-domain inverse technique for the localization and quantification of rotating sound sources. (June 2017) - Zhang, Xiao-Zheng; Bi, Chuan-Xing; Zhang, Yong-Bin; Xu, Liang
Highlights: A time-domain inverse technique is proposed to study rotating sound sources. The model is constructed based on the time-domain equivalent source method. This inverse technique is able to quantify sound fields compared to beamforming. The accurate localizations in the low-frequency domain can be guaranteed. Abstract: A time-domain inverse technique based on the time-domain equivalent source method is proposed for the localization and quantification of rotating sound sources. In this technique, the actual rotating sound sources are modeled by a series of rotating equivalent sources distributed on the source surface. The strengths of these equivalent sources are solved based on the exact transfer relationship between the measured pressure at the receiver time and the desired equivalent source strengths at the source time. Compared to the known time-domain rotating beamforming that just owns the function of source localization, the proposed inverse technique not only can locate rotating sources accurately but also can predict sound fields quantitatively. Moreover, due to the use of retarded time approach, the proposed inverse technique avoids the interpolation of measured pressure that is needed in the time-domain rotating beamforming, thus providing the ability of real-time calculation of source strengths. Numerical simulations and experiments examine the validity of the proposed technique and demonstrate its advantages of locating sources more accurately and enabling to predict sound fields quantitatively by comparing with the time-domain rotating beamforming.